A 271.8 nm deep-ultraviolet laser diode for room temperature operation. (7th November 2019) - Zhang, Ziyi; Kushimoto, Maki; Sakai, Tadayoshi; Sugiyama, Naoharu; Schowalter, Leo J.; Sasaoka, Chiaki; Amano, Hiroshi
Abstract: We present a deep-ultraviolet semiconductor laser diode that operates under current injection at room temperature and at a very short wavelength. The laser structure was grown on the (0001) face of a single-crystal aluminum nitride substrate. The measured lasing wavelength was 271.8 nm with a pulsed duration of 50 ns and a repetition frequency of 2 kHz. A polarization-induced doping cladding layer was employed to achieve hole conductivity and injection without intentional impurity doping. Even with this undoped layer, we were still able to achieve a low operation voltage of 13.8 V at a lasing threshold current of 0.4 A.